Development and applications of chromosome-specific cytogenetic BAC-FISH probes in Larimichthys crocea - Zhang, Jianpeng; Xie, Jingyi; Liu, Bo; Wang, Zhiyong; Wang, Yilei; Jiang, Yonghua; Zhang, Jing; Cai, Mingyi (Frontiers in Marine Science, 2022)
Large yellow croaker Larimichthys crocea (Richardson) is an important member in family Sciaenidae, and one of most productive mariculture fishes in China. Fluorescence in situ hybridization is a useful tool for cytogenetics and genomics research. Here, we demonstrated that bacterial artificial chromosome (BAC) clones could be used to identify individual chromosomes in large yellow croaker, and also to study chromosome evolution in the related species. By using BAC paired-end sequencing and sequence alignment, 435 BAC clones were anchored to 24 pseudochromosomes of large yellow croaker genome. Among them, 72 BAC clones with low repeat content were selected and passed PCR test, and then grouped by chromosome for FISH test. As a results, there were 67 BAC clones, 2 to 3 BAC clones per chromosome, generated specific and stable signal at expected position. Then, a dual-color FISH probe cocktail composed of 48 of these BAC clones was formulated and used to hybridize metaphase chromosome spreads, resulting in distinct signal patterns on each chromosome pair, which help to distinguish all chromosomes in the metaphase spreads of large yellow croaker. The chromosome-specific BAC-FISH probes were also applied to a close relative of large yellow croaker, Collichthys lucidus, demonstrating that its Y chromosome originated from the fusion of Chr.1 and Chr.7. Thus, our study provides the first set of chromosome-specific FISH probes in family Sciaenidae, which will play an important role in cytogenetics and genomics research in the family.